An Adaptive Cross-Tied Interconnection for Shaded PV Arrays: A Mathematical Analysis for Efficiency Enhancement - Efendi S Wirateruna; Mohammad Jasa Afroni; Wahyu Mulyo Utomo; Mukhammad Zakky Syahrul Aziz (Universitas Muhammadiyah Malang, 2026)
This study investigates the Adaptive Cross-Tied Interconnection (ACTI) configuration to improve the power output efficiency of photovoltaic (PV) arrays operating under partial shading conditions. The objective of this study is to develop a mathematical formulation that describes the behavior of ACTI compared to the conventional Series-Parallel (SP) configuration. Mathematical modeling is used to analyze the current distribution, voltage relationships, and the effect of shading patterns on the total output power. Simulations are performed using MATLAB/Simulink to verify the theoretical analysis results. This adaptive configuration dynamically adjusts the cross-tied interconnections based on the illumination intensity data, thereby balancing the current between shaded and non-shaded modules. The results show that ACTI successfully reduces current mismatch losses and increases output power without increasing circuit complexity. In a 3×3 PV array, the ACTI configuration yields a power increase of up to 48% compared to the SP configuration. In a 5×5 array, the efficiency increases ranges from 2% to 6%, depending on the shading pattern. The adaptive switching strategy maintains the current flow stability and produces a smoother power-voltage curve, enabling faster and more accurate tracking of the global maximum power point. These results demonstrate that ACTI provides an efficient, economical, and mathematically sound solution for improving the performance of PV systems under non-uniform irradiation conditions.